2019
DOI: 10.2478/emj-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of personal variables on entrepreneurial intention: A comparative study between Poland and Spain

Abstract: This article analyses the influence of personal variables on entrepreneurial intentions of students from Poland and Spain. The article presents an integrated structural model that has been developed from a set of student perceptions from both countries. A small number of variables included in the model allows explaining and managing the formation of the intention in the context of higher education. This study provides answers to the following questions: What role do personal variables play as motivation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 80 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Taking into account that the young people of Spain and Poland value very positively all the observed variables presented, given the high scores of the items, it is concluded that this segment of the population has a favorable predisposition to entrepreneurship in both countries. This predisposition favors action in the educational context and through other institutions to promote entrepreneurship, and thus, contribute to the sustainable development of regions [182][183][184][185]. As such, policymakers can use the findings of this research to establish policies to improve the conditions in the ecosystems for sustainable entrepreneurship in their regions.…”
Section: Conclusion Implications and Limitationsmentioning
confidence: 93%
“…Taking into account that the young people of Spain and Poland value very positively all the observed variables presented, given the high scores of the items, it is concluded that this segment of the population has a favorable predisposition to entrepreneurship in both countries. This predisposition favors action in the educational context and through other institutions to promote entrepreneurship, and thus, contribute to the sustainable development of regions [182][183][184][185]. As such, policymakers can use the findings of this research to establish policies to improve the conditions in the ecosystems for sustainable entrepreneurship in their regions.…”
Section: Conclusion Implications and Limitationsmentioning
confidence: 93%
“…The literature shows a trend related to the search for appropriate competences that should characterise an educated entrepreneur (Gonzalez & Kobylinska, 2019) so that one can successfully (Jain, 2011;Lewrick et al, 2010) and in a sustainable way (Coyne, 2016) carry out his work. Already in the 80s, Ronstadt pointed out that entrepreneurship and related competences can and must be mastered (Ronstadt, 1987).…”
Section: Theoretical Framework and Research Methodsmentioning
confidence: 99%
“…Perceived behavioral control constitutes individuals' beliefs in their ability to achieve a certain behavior, based on extensive knowledge, experience, and skills [47]. In this study, perceived behavioral control refers to the individual's ability to assess factors to promote their entrepreneurship; the literature generally agrees that the perception of being in control is positively related to the intention to become an entrepreneur [48,49]. Relevant empirical studies also show that perceived behavioral control plays a partially mediating role on the impact of college students' entrepreneurial intention.…”
Section: Effects Of Entrepreneurial Attitude Entrepreneurial Self-eff...mentioning
confidence: 98%